The existence of bureaucratic network governance in optimizing the role of districts institution - Donald K. Monintja; Alfon Kimbal; Neni Kumayas; Katerina Bataha (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the existence of bureaucratic network governance in optimizing the role of district institutions in Kumelembuai District, South Minahasa Regency. The change in the status of the sub-district as a regional apparatus, following Law Number 23 of 2014, has shifted the sub-district's functions toward greater coordination. However, the district remains an important node in the delivery of government services, public services, and community empowerment. This research uses a qualitative approach, employing case study methods that include observation, interviews, and documentation. The study's results show that limited authority, a lack of human resources, and weak coordination across sectors are the main obstacles to optimizing district institutions. However, there are local initiatives, such as the appointment of district staff as acting village heads, that demonstrate leadership potential and adaptability in the bureaucracy. This research emphasizes the importance of strengthening governance within the bureaucratic network through training, competency adjustments, and broader delegation of authority. These findings are expected to make a significant contribution to formulating policies that strengthen district institutional capacity in the era of regional autonomy.